MOBILE TOOL IN EVALUATING THE WELFARE OF DAIRY CATTLE - Oliveira Júnior, A. J.; Souza, S. R. L.; Souza, V. C.; Costa, N. Z.; Bueno, L. G. F.; Almeida, R. A. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The climatic elements can influence the animal performance in a negative way, in this way one must act in order to minimize its effects, using suitable constructions to shelter them. The climatic differences between the country of origin of dairy cattle and Brazil prevent cows from expressing their genetic potential for milk production as a function of thermal stress, especially during the summer, where high temperatures and relative humidity are observed air. The objective of this work was to use the mobile tool Dewel® to calculate comfort indexes aiming the welfare of dairy cows. Environmental variables were collected in the cow resting shed after milking, such as: Dry Bulb Temperature (Tbs), Black Globe Temperature (Tgn) and Relative Humidity (RH). After collecting the environmental data, the ITGU and ITU thermal comfort index was calculated through the Orvalho® application to infer the thermal stress state of the animals. As a result, the values ​​presented are within the limits of comfort for dairy cows (ITGU max = 72,03 and ITU max = 72,46). The Orvalho® app helped in a practical way the calculation of the indexes studied, proving to be a useful mobile resource for small evaluations of thermal conditions.